DYNAMICS OF THE PRO-INFLAMMATORY AND ANTI-INFLAMMATORY CYTOKINES DURING A WHOOPING COUGH IN CHILDREN OF THE FIRST YEAR OF LIFE - N.M. KHODZHAEVA; M.D. MADZHONOVA (Avicenna Tajik State Medical University, 2018)
Objective: To study the state of cytokine status in the dynamics of the disease and find out its role in the course of a whooping cough in children of the first year of life. Methods: Twenty children have surveyed at the age of 1-year-old with a diagnosis of a whooping cough, which formed the main group, as well as 30 practically healthy children of the same age who formed the control group. The concentration of pro-inflammatory cytokines (IL-6, IFN-γ) and the anti-inflammatory cytokine (IL-4) studied by enzyme immunoassay. Results: The analysis of the peculiarities of the cytokine profile in patients with whooping cough showed that the most significant violations concerned the ability of lymphocytes to produce IFN-γ, which was low, starting from the 2nd week, and throughout the disease in all variants of whooping cough. Also paid attention to the active products the of one of the pro-inflammatory cytokines IL-6, which exceeded control value in half and more. The level of antiinflammatory cytokine IL-4 was not significantly different from such of practically healthy children. Conclusion: Multidirectional changes in the level of cytokines in the dynamics of the infectious process and depending on the severity of the pathological process, allowing predicting the current outcome of this infection. Analysis of the obtained data revealed a correlation of different levels between pro-inflammatory and anti-inflammatory cytokines, which play an important role in inflammatory mediators during whooping cough in children.